Photochemically activated 3D printing inks: Current Status, Challenges, and Opportunities - Gauci, Steven; Vranic, Aleksandra; Blasco, Eva; Bräse, Stefan; Wegener, Martin; Barner-Kowollik, Christopher (Advanced materials, 2024)
3D printing with light is enabled by the photochemistry underpinning it. Without fine control over the ability to photochemically gate covalent bond formation by the light at a certain wavelength and intensity, advanced photoresists with functions spanning from on-demand degradability, adaptability, rapid printing speeds, and tailored functionality are impossible to design. Herein, recent advances in photoresist design for light-driven 3D printing applications are critically assessed, and an outlook of the outstanding challenges and opportunities is provided. This is achieved by classing the discussed photoresists in chemistries that function photoinitiator-free and those that require a photoinitiator to proceed. Such a taxonomy is based on the efficiency with which photons are able to generate covalent bonds, with each concept featuring distinct advantages and drawbacks.
Gesehen am 25.01.2024